Chemically linked metal-matrix nanocomposites of boron nitride nanosheets and silver as thermal interface materials. (31st January 2018) - Nagabandi, N; Yegin, C; Feng, X; King, C; Oh, J K; Scholar, E A; Narumanchi, S; Akbulut, M
Abstract: Herein, novel hybrid nanocomposite thermal interface materials (TIMs) relying on the chemical linkage of silver, boron nitride nanosheets (BNNSs), and organic ligands are reported. These TIMs were prepared using a co-electrodeposition/chemisorption approach where the electrolytic reduction of silver ions into silver nano-/micro-crystals was coupled with the conjugation of ligand-coated nanosheets onto silver crystals. Furthermore, the influence of the bond strength of silver/nanosheet links on the thermal, mechanical, and structural properties is investigated using a combination of techniques including laser flash analysis, phase-sensitive transient thermoreflectance, nanoindentation, and electron microscopy. The internal nanostructure was found to be strongly dependent on the linker chemistry. While the chemical grafting of 4-cyano-benzoyl chloride (CBC) and 2-mercapto-5-benzimidazole carboxylic acid (MBCA) on BNNSs led to the uniform distribution of functionalized-nanosheets in the silver crystal matrix, the physical binding of 4-bromo-benzoyl chloride linkers on nanosheets caused the aggregation and phase separation. The thermal conductivity was 236–258 W m −1 K and 306–321 W m −1 K for physically and chemically conjugated TIMs, respectively, while their hardness varied from 400–495 MPa and from 240 to 360 MPa, respectively. The corresponding ratio of thermal conductivity to hardness, which is a critical parameter controlling the performance of TIMs, was ultrahigh for the chemically conjugated TIMs: 1.3 × 10 −6 m 2 K −1 s for MBCA-BNNS and 8.5 × 10 −7 m 2 K −1 s for CBC-BNNS. We anticipate that these materials can satisfy some of the emerging thermal management needs arising from the improved performance and efficiency, miniaturization, and/or high throughput of electronic devices, energy storage devices, energy conversion systems, light-emitting diodes, and telecommunication components.